Management Education in Public Health: Further Considerations; Comment on "Management Matters: A Leverage Point for Health Systems Strengthening in Global Health" - Kurt J. Darr (Kerman University of Medical Sciences, 2015)
Knowing and applying the basic management functions of planning, organizing, staffing, directing, and controlling, as well as their permutations and combinations, are vital to effective delivery of public health services. Presently, graduate programs that prepare public health professionals neither emphasize teaching management theory, nor its application. This deficit puts those who become managers in public health and those they serve at a distinct disadvantage. This deficit can be remedied by enhanced teaching of management subjects.